ANALISIS KOMBINASI LARUTAN AB MIX DAN POC AIR CUCIAN BERAS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY DI BAWAH PEMBIBITAN SELADA SISTEM RUMAH PLASTIK - Rachmi Hariaty Hasan; Eka Febrianti; Hijria Hijria; Andi Awaluddin; Agustono Agustono; Agung Setiawan; Hadi Riyandi (Universitas Andi Djemma Palopo, 2022)
The concept of planting, especially in urban areas, is very suitable for implementing a hydroponic system, given the increasingly narrow condition of agricultural land. Plant nutrition using AB Mix Solution is considered to be expensive and also contains chemicals. The combination of AB Mix and POC rice washing water is expected to support the growth and yield of Pakcoy plants to the maximum. The selection of horticultural plants (Pakcoy) is due to the nutritional value and benefits of the vegetable plants themselves. The research was conducted in Experimental Field 1 and Lab. Agrotechnology Agronomy Unit, Faculty of Agriculture, by applying a Completely Randomized Design located under the lettuce nursery in a plastic house. The treatments include 100% AB Mix + 0% POC, 80% AB Mix + 20% POC, 60% AB Mix + 40% POC, 40% AB Mix + 60% POC, and 20% AB Mix + 80% POC. . The parameters to be observed consisted of plant height (cm), leaf length (cm), number of leaves (strands), and leaf width (cm), average wet weight of plants, and dry weight of shoots and roots (gr) calculated by drying yields using an oven at a temperature of 80Â 0C for 2 x 24 hours. The results showed that there was no significant difference between the combination of AB Mix and POC for all variables with P3 treatment showing higher parameter values than others. However, for the wet weight measurement, P0 showed a higher yield, due to the high water content in the plant